Evolution and human culture : texts and contexts - Tague, Gregory. (Value Inquiry Book Series, 2016)
Evolution and Human Culture argues that values, beliefs, and practices are expressions of individual and shared moral sentiments. Much of our cultural production stems from what in early hominins was a caring tendency, both the care to share and a self-care to challenge others. Topics cover prehistory, mind, biology, morality, comparative primatology, art, and aesthetics. The book is valuable to students and scholars in the arts, including moral philosophers, who would benefit from reading about scientific developments that impact their fields. For biologists and social scientists the book provides a window into how scientific research contributes to understanding the arts and humanities. The take-home point is that culture does not transcend nature; rather, culture is an evolved moral behavior.